Factors Motivating the Adoption of Geographical Indication-Based Quality Standards among Robusta Coffee Farmers in Indonesia - Hanifah Ihsaniyati; Nuning Setyowati; Pardono (International Journal of Business and Society, 2022)
Robusta coffee is one of the superior commodities of the Temanggung Regency. As the quality of a coffee determines its market competitiveness, geographical indications (GIs) are one of the quality standards used in coffee cultivation and post-harvest processing to indicate the quality of a good Robusta coffee. However, most Robusta coffee farmers in Indonesia do not practice the production methods required to meet these standards. Therefore, the produced coffee does not meet the quality standards of consumers. As such, this study aimed to analyse the factors that may motivate or dissuade farmers from adopting GI-based quality standards for Robusta coffee in Temanggung Regency. A descriptive method; specifically, a survey; was used for data collection. This data was then analysed using the partial least squares (PLS) method. The findings of this study revealed that, while knowledge did not motivate the adoption of GI standards, optimising collaboration between farmers and relevant associations may increase the adoption of GI-based quality standards among Robusta coffee farmers in Temanggung Regency.